Metode Fuzzy Logic Dalam Visualisasi Sterilisasi Buah Kelapa Sawit Menggunakan Ladder Diagram - Ananda Hadi Elyas (Query: Journal of Information Systems, 2019)
The process of sterilizing palm fruit with a capacity of thousands of kilograms is carried out using saturated steam with a temperature of ± 132º C which is a process that greatly affects the quality of the palm oil produced. The amount of fruit and the amount of pressure are the parameters that affect the duration of the boiling process, thus, the exact calculation of boiling time is needed so that the quality produced will be optimal. The Fuzzy Logic method which has been widely developed in the field of control systems can be used as an alternative in designing a control system capable of carrying out the sterilization process by considering the amount of fruit and the amount of pressure used in the boiling process so that it can predict the length of the boiling process that will run based on the rules that have been implanted. Fuzzy logic method in the control system can be simulated using ladder diagrams and tested before the system designed is implanted with the control system device used, which is Programmable Logic Control (PLC). Applying the Fuzzy logic method that is embedded in the PLC, the boiling process can be run more optimally by providing parameters of the number of pieces and the amount of pressure as input, then the control system can predict the length of time the boiling process will be run.Keywords:  Fuzzy Logic, Ladder Diagram, PLC, Sterilization